The Influence of Product Quality, Service Quality, and Location on Loyalty Customers of Lontong Balap Pak Gendut Surabaya - Angga Widi Kristianto; Agus Baktiono (Journal of World Conference (JWC), 2020)
Customer loyalty is an important key to maintaining the position of the company in the market and creating efficiency and effectiveness of the company because if the company does not build customer loyalty then the possibility of companies having to spend more and more energy to find new customers Therefore this study aims to analyze whether product quality, service quality, and location can affect customer loyalty to make repurchases at that place. This research is quantitative research and multiple linear regression analysis with a sample of 160 respondents. Furthermore, there are four variables used in this study, namely product quality (X1), service quality (X2), location (X3), and customer loyalty (Y). Data collection was obtained from the distribution of questionnaires to customers of Lontong balap mr.Gendut at Surabaya. The results show that product quality variables (X1), service quality (X2), and location (X3) simultaneously have a significant effect on customer loyalty (Y). Then variable product quality (X1), service quality (X2), and location (X3) partially have a significant effect on customer loyalty (Y). Based on the results of this study, business owners of Lontong Balap should maintain product quality, service quality and location placement so that customers remain and always buy at that pleace.